2020
DOI: 10.3389/frph.2020.00007
|View full text |Cite
|
Sign up to set email alerts
|

Transitions: Novel Study Methods to Understand Early HIV Risk Among Adolescent Girls and Young Women in Mombasa, Kenya, and Dnipro, Ukraine

Abstract: Transitions aims to understand the human immunodeficiency virus (HIV) risk at critical transition points in the sexual life course of adolescent girls and young women (AGYW) who engage in casual sex, transactional sex, and sex work. In this article, we present the Transitions study methods. The Transitions study has the following objectives: (1) to describe how the characteristics and length of the transition period and access gap vary across two epidemiological contexts (Mombasa, Kenya, and Dnipro, Ukraine); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The study was conducted in Kisauni sub‐county, one of the six sub‐counties in Mombasa, Kenya. Key population size estimation conducted in 2014 showed that Kisuani had the highest number of YWSS compared to other sub‐counties (41% of the total estimated YWSS population) [ 8 ]. ICRH‐K, the implementing partner in the project, has a long‐standing HIV prevention programme with FSWs in the county.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted in Kisauni sub‐county, one of the six sub‐counties in Mombasa, Kenya. Key population size estimation conducted in 2014 showed that Kisuani had the highest number of YWSS compared to other sub‐counties (41% of the total estimated YWSS population) [ 8 ]. ICRH‐K, the implementing partner in the project, has a long‐standing HIV prevention programme with FSWs in the county.…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, there were an estimated 15,000 female sex workers (FSWs) <below 18 years of age in Kenya [ 7 ]. Mapping and size estimation data from the Transitions study [ 8 ] conducted in sex work venues in Mombasa, Kenya, have shown that 52% of all estimated FSWs were 14–24 years old [ 9 ], with an HIV prevalence of 10% among self‐identified YWSS compared to 4% among non‐YWSS of the same age [ 10 ]. The same study also revealed that YWSS in these venues reported higher experience of violence compared to those who were not selling sex [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Transitions study is a cross-sectional integrated biological and behavioural survey conceived to measure the prevalence and patterns of HIV risk and vulnerabilities 26 28 . From March to December 2015, field teams in the city of Dnipro, Ukraine administered written informed consent, conducted interviews, and oversaw multiplex rapid testing for HIV, syphilis, and hepatitis B and C (Profitest Combo, New Vision Diagnostics, Haicang Xiamen, China) among study participants.…”
Section: Methodsmentioning
confidence: 99%
“…Data collection continued until the target sample of 560 participants had been interviewed, facilitated by the close cooperation of social mobilizers, who communicated the importance and relevance of the study to participants. Survey questions were informed by Integrated Biological and Behavioral Survey Guidelines ( 23 ), as well as other sex worker surveys, including the Transitions study ( 24 ), an earlier study piloted and locally validated in Dnipro. Participants were asked questions about basic socio-demographics, experiences of sex work, access to HIV prevention and care programs and related services, and HIV testing behaviors.…”
Section: Methodsmentioning
confidence: 99%